Bangladesh Education Sector Review : Seeding Fertile Ground - Education that Works for Bangladesh - World Bank (Dhaka, 2014)
This series of policy notes (PNs) aims to support, over the medium term, a coherent and articulated policy dialogue on education and skills development that will help Bangladesh achieve its target of becoming a middle-income country. The main findings and key policy directions related to the three PNs are provided next, in section two. These findings are presented in a concise manner to remain relevant and useful for a diverse audience. A policy matrix also shows the cumulative findings of the PNs. Further work will be required to sequence these policy options. An analysis of costs of these policy levers will also be highly fruitful in determining the optimal mix of policy interventions.